Sacrificing one visual hemifield during pediatric epilepsy surgery: Effects on visual search. (November 2020) - Neumayr, Lisa; Gschaidmeier, Alisa; Trauzettel-Klosinski, Susanne; Pieper, Tom; Kudernatsch, Manfred; Hofer, Wiebke; Bajer, Christina; Staudt, Martin
Abstract: Objectives: To investigate early and late effects of planned surgically acquired homonymous hemianopias on visual search in children and adolescents. Methods: This prospective study included five patients (5y 5 m–18y 0 m; 2 girls) with pharmaco-refractory epilepsies in whom one visual hemifield was sacrificed as part of the surgical strategy, and, as controls, seven patients (5y 11 m–18y 0 m; 6 girls) undergoing epilepsy surgeries not affecting the visual fields. Visual search was studied using the "Table Test", which is an everyday life-like visual search test. General processing speed was studied using a standard IQ subtest. Results: All five patients with newly acquired homonymous hemianopias showed a relative disadvantage of visual search times for objects in their newly blind hemifields immediately after the surgery. Six months later, this relative disadvantage had recovered completely in all patients. Nevertheless, compared with the preoperative situation, overall search times were still prolonged in the hemianopic patients, but this effect could be mitigated or even overcompensated by improvements in processing speed. Conclusions: Children with homonymous hemianopias inflicted by epilepsy surgery develop effective compensation strategies to minimize the relative disadvantage of visual search in their blind hemifields. For changes in overall visual search times between the preoperative and the six-month follow-up examination, we could demonstrate overlapping effects of (a) deterioration by hemianopia and (b) amelioration by improved processing speed as part of the cognitive improvements achieved by amelioration of the epilepsy. Highlights: Prospective study (pre/post) on visual search in newly acquired iatrogenic hemianopia. New hemianopia causes visual search disadvantage in the newly blind hemifield. Six months later, this relative disadvantage is compensated.